Epstein-Barr Virus Antibodies in Rheumatoid Arthritis Iraqi patients - Al-Derzi, Aida R.; Alani, Muhammad M.; AL-Hadithi, Hayfaa S. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Rheumatoid arthritis (RA) is an autoimmune disease that results in a chronic, systemic inflammatory disorder that may affect many tissues and organs, but principally attacks flexible (synovial) joints. Many cases are believed to result from an interaction between genetic factors and environmental exposures. Epstein-Barr virus (EBV) is associated with several autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis and multiple sclerosis. Objective: To study the association between EBV antibodies and RA. Patients and methods: This prospective study was carried out in the period between March 2013 and May 2013. The study involved 30 patients diagnosed with RA attending rheumatology outpatient’s clinic Baghdad medical city teaching hospital and 30 apparently healthy individuals as a control group. Serum samples were collected to investigate the level of EBV-IgG and IgM by using ELISA technique. Results: This study showed that 70% of control group had positive EBV-IgG while only 6 out of 30 had positive EBV-IgM. The mean values of EBV-IgG were significantly higher among RA patients (0.542 IU/ml) in comparison with that in control group(0.269 IU/ml). Also mean value of serum EBV-IgM (0.723 IU/ml) were significantly higher than that in healthy individuals(0.354 IU/ml) Conclusions: The serum levels of EBV-IgG and IgM were significantly higher in RA patients in contrast with those in healthy individuals